Capital Market Integration : Progress Ahead of the East African Community Monetary Union - Yabara, Masafumi (Washington, D.C. : International Monetary Fund, 2012)
Capital markets in the East African Community (EAC) face common challenges of low capitalization and liquidity, but to different degrees. EAC member countries have made noticeable progress in developing domestic capital markets through a regional approach, removing constraints on capital transactions and harmonizing market infrastructure. Nevertheless, empirical analysis suggests capital market integration has not deepened during the past few years in the EAC, although convergence of investment returns is taking place to some extent. Learning from the experience of the West African Economic and Monetary Union and the Association of Southeast Asian Nations, EAC countries would benefit from four actions to accelerate financial market integration: (i) further harmonize market infrastructure; (ii) strengthen regional surveillance mechanisms; (iii) encourage local currency bond issuance by multilateral financial institutions; and (iv) build the capacity of the existing regional institutions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet